Estudio farmacognóstico preliminar de las semillas de moringa oleífera lam cultivada en Machala. - Herrera Romero, Omayra Juliana (2015)
The investigation of moringa seeds grown at the Technical University of Machala, which, after drying, were evaluated some pharmacognostic parameters.